Fire resistance tests on beam-to-column shear connections - Palma, P. (2014)
This paper presents the results of an extensive experimental campaign on the fire behaviour of beam-to-column timber connections loaded perpendicular-to-the-grain. The experimental campaign addressed the fire behaviour of beam-to-column timber shear connections in a systematic way, testing a wide range of common connection typologies, significantly enlarging their experimental background